Interpreting Pontormo’s Halberdier: Francesco Guardi or Cosimo I de’ Medici? - Kholev, Roman R. (Actual Problems of Theory and History of Art, 2021)
Jacopo Pontormo’s Portrait of a Halberdier is one of the most discussed Florentine portraits of the Cinquecento. The dispute concerns the identification of the model which is interpreted as the Florentine noble Francesco Guardi, defender of the Florentine Republic struggling against the Medici during the Siege in 1529–1530, or the Duke Cosimo I de’ Medici. This article aims to methodize different approaches to identify the young halberdier represented in historiography, to evaluate recent studies on this subject and to analyze why the Pontormo’s portrait admits directly opposing monarchic (Cosimo de’ Medici) and republican (Francesco Guardi) interpretations. The study is based on the analysis of Florentine court culture formed in the 16th century and the representation of Duke Cosimo de’ Medici in the Florentine art.As a result, the author distinguished the iconological and the anatomical approaches proposed by scholars to identify Pontormo’s Halberdier. The anatomical study, which identified the halberdier as Cosimo I in reason of their similar hands’ deformities, is criticized. Duke’s pathology, depicted in some of Bronzino’s portraits, is considered as a sign of beauty and uniqueness adopted by the painter from Pontormo’s portrait. The author supported Elisabeth Cropper’s interpretation, which considered the sitter as Francesco Guardi. The iconological ambivalence of the portrait permitting its medicean and anti-medicean interpretations is explained by the nature of Florentine court culture and Cosimo’s representation, which assimilated ancient republican symbols of Florence and used it to glorify the Duke and the Medici dynasty.
Keywords: portrait; Florence; Renaissance; mannerism; iconology; Pontormo; halberdier; Cosimo; Medici